New taxa of Trigonidiini (Orthoptera: Grylloidea: Trigonidiidae: Trigonidiinae) from China - Ma, Libin; Pan, Zhaohui (Zootaxa, 2019)
Sectus gen. nov. was proposed on the basis of genitalic features. Two new combinations have resulted, Sectus peruviana (Chopard, 1956) comb. nov. and Sectus hainanensis (He et al., 2010) comb. nov. Three new species, Anaxipha nigritorquis sp. nov., Metiochodes gracilus sp. nov. and Sectus integrum sp. nov., are described and illustrated.